The Effectiveness of Using Youtube for Vocabulary Mastery - Dwi Heriyanto (Universitas PGRI Semarang, 2015)
The study is to examine the improvement in vocabulary comprehension and maintenance of English as foreign language students at SMK Maárif 1 of Kebumen because of this of integrating YouTube in their reading classes. The study also investigated the perceptions of both students as well as teachers towards the inclusion of YouTube on the development of vocabulary. One hundred intermediate level learners aged between 14-17 years old participated in the study. Students were divided into two organizations: an experimental group who watched YouTube during the reading activities and a control group who was not exposed to the videos. Data were collected using pre-tests and post-tests in addition to questionnaires. The findings of the analysis reveal that the group who viewed the YouTube clips outperformed the group who was simply not subjected to YouTube videos in the posttest. The results clearly show that YouTube offered statistically significant effects on the students' vocabulary acquisition. The findings of the study indicate that the participants positively viewed the use of YouTube in their lessons. The findings also exposed significant improvement in the students’ vocabulary achievement. The implications of the findings are discussed within the context of foreign language learning and teaching